An effective optimization approach for load frequency control of off-grid delayed fuel cell microgrid - Celik, Vedat (Pergamon-Elsevier Science Ltd, 2024)
This paper presents a powerful performance optimization approach for load frequency control in the off-grid mode of a delayed fuel cell microgrid with PI controller. The new approach based on stability boundary locus is used. Thanks to this, the search is only carried out in PI control parameter space keeping stable the system in the proposed optimization. The superiority of the proposed approach in terms of iteration history, fitness values, and time responses of the system is presented by comparing the results obtained. According to the results obtained, the proposed approach reaches the global minimum in a very short number of iterations and achieves this by both guaranteeing the stability of the system and providing the desired time response performances compared to the other method.
Keywords: Renewable energy; Delayed fuel cell microgrid; Chaos embedded particle swarm optimization; PI controller; Stability boundary locus